2019
DOI: 10.1542/peds.2018-1988
|View full text |Cite
|
Sign up to set email alerts
|

Foreign-Body Ingestions of Young Children Treated in US Emergency Departments: 1995–2015

Abstract: OBJECTIVES: To describe the epidemiology of foreign-body ingestions (FBIs) of children <6 years of age who were treated in US emergency departments from 1995 to 2015. METHODS: We performed a retrospective analysis using data from the National Electronic Injury Surveillance System for children <6 years of age who were treated because of concern of FBI from 1995 to 2015. National estimates were generated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
84
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 21 publications
14
84
5
3
Order By: Relevance
“…The analysis of 1199 accidental paediatric foreign body and chemical substance ingestions over thirteen years (2005-2017) at a German University Medical Centre revealed a signi cant increase in the annual case rate of 80% to about 11 per 10.000 children in the catchment area. This has also been reported in the United States with an annual increase of 91.5% from 9.5 in 1995 to 18 per 10.000 children with FBI in 2015 [7]. In contrast, considerably less FBI have been reported at Chiang Mai University in Thailand (only 194 cases from 2006 to 2017) with a population comparable to Ulm.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The analysis of 1199 accidental paediatric foreign body and chemical substance ingestions over thirteen years (2005-2017) at a German University Medical Centre revealed a signi cant increase in the annual case rate of 80% to about 11 per 10.000 children in the catchment area. This has also been reported in the United States with an annual increase of 91.5% from 9.5 in 1995 to 18 per 10.000 children with FBI in 2015 [7]. In contrast, considerably less FBI have been reported at Chiang Mai University in Thailand (only 194 cases from 2006 to 2017) with a population comparable to Ulm.…”
Section: Discussionsupporting
confidence: 57%
“…the world [2,3,6,25,26]. A variety of foreign bodies is ingested of which coins appear the most common in our cohort like in many other studies [2,7,25,27,28]. However, the share was lower in our study (18%) compared to 49 to 88% reported by others, which may also re ect changes over time, differences in referral, selection and inclusion of the patients or classi cation and localization of objects as well as different diets and habits of the populations [2,26,[28][29][30].…”
Section: Ingestion Of Foreign Bodies or Chemical Substances Is Frequesupporting
confidence: 59%
See 2 more Smart Citations
“…While coins, balls, and pearls are some of the more commonly ingested/aspirated items [2], clinicians must maintain a high degree of suspicion for magnets and batteries, due to their potential for serious and even fatal sequelae. A particularly dangerous subset of magnets is small rare-earth magnets such as neodymium magnets, which are substantially stronger than traditional ferrite magnets [3,4]. Ingestion of multiple of these "supermagnets" is of special concern, as they can attract through intestinal walls, resulting in pressure necrosis, fistulization, and bowel perforation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%